Intracellular delivery of nano‐formulated antituberculosis drugs enhances bactericidal activity. Issue 3 (2nd October 2017) - Donnellan, Samantha; Stone, Vicki; Johnston, Helinor; Giardiello, Marco; Owen, Andrew; Rannard, Steve; Aljayyoussi, Ghaith; Swift, Benjamin; Tran, Lang; Watkins, Craig; Stevenson, Karen
Abstract: Tuberculosis kills more people worldwide than any other infectious disease. Treatment requires multiple drug therapy administered over long periods (6–24 months). The emergence of multidrug‐resistant strains is a major problem, and with few new drugs in the pipeline, a novel modus operandi is urgently required. Solid drug nanoparticles (SDNs), a new development in nanomedicine, offer a fresh therapeutic approach. Here, we show that SDNs are more effective (50‐fold) at killing pathogenic mycobacteria than aqueous forms of the same drug and can target mycobacteria internalised by macrophages, where bacilli reside. We demonstrate synthesis of dual and triple drug loaded SDNs, facilitating combination tuberculosis therapy. Our results suggest that by employing SDNs of existing antibiotics, it may be possible to improve drug delivery and therefore reduce drug dosage to lessen side effects and fight drug resistance. Abstract : Tuberculosis (TB), caused by Mtb, is a global crisis. It is very difficult to treat, requiring multidrug therapy over many months. Solid drug nanoparticles (SDNs) are nanosized amorphous particles, constructed of active pharmaceutical ingredients and are a novel development in nanotechnology. The anti‐mycobacterial properties of SDNs were created of the first‐line antibiotics used to treat TB. Compared with conventional antibiotics, SDNs were found to be more effective (50‐fold) at killing pathogenic mycobacteria and could target bacilli internalised by macrophages.